Local temperature increases reduce soil microbial residues and carbon stocks - Zeng, Xiao‐Min; Feng, Jiao; Yu, Dai‐Lin; Wen, Shu‐Hai; Zhang, Qianggong; Huang, Qiaoyun; Delgado‐Baquerizo, Manuel; Liu, Yu‐Rong (Global change biology, 2022)
Warming is known to reduce soil carbon (C) stocks by promoting microbial respiration, which is associated with the decomposition of microbial residue carbon (MRC). However, the relative contribution of MRC to soil organic carbon (SOC) across temperature gradients is poorly understood. Here, we investigated the contribution of MRC to SOC along two independent elevation gradients of our model system (i.e., the Tibetan Plateau and Shennongjia Mountain in China). Our results showed that local temperature increases were negatively correlated with MRC and SOC. Further analyses revealed that rising temperature reduced SOC via decreasing MRC, which helps to explain future reductions in SOC under climate warming. Our findings demonstrate that climate warming has the potential to reduce C sequestration by increasing the decomposition of MRC, exacerbating the positive feedback between rising temperature and CO2 efflux. Our study also considered the influence of multiple environmental factors such as soil pH and moisture, which were more important in controlling SOC than microbial traits such as microbial life‐style strategies and metabolic efficiency. Together, our work suggests an important mechanism underlying long‐term soil C sequestration, which has important implications for the microbial‐mediated C process in the face of global climate change. The contribution of microbial residue carbon (MRC) to soil organic carbon (SOC) was dependent on local temperature along two independent elevation gradients. Local temperature increases could reduce SOC accumulation mainly by decreasing MRC due to the increasing MRC decomposition. Our study also considered the influence of multiple environmental factors such as soil pH and moisture, which were more important in controlling SOC than microbial traits such as microbial life‐style strategies and metabolic efficiency. Our work suggests an important mechanism underlying long‐term soil carbon sequestration, which has important implications for the microbial‐mediated carbon process under global climate change.